The Role of Political Party Witnesses in Supervising Vote Counting in Indonesia - Muhammad Syafwan Saufi; Soraya Oktarina (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
Elections in Indonesia are a cornerstone of democracy, but the complexity of vote counting often presents challenges in maintaining the integrity of election results. Political party witnesses play a strategic role as supervisors to ensure transparency and accuracy in the vote counting process at polling stations (TPS). This research aims to analyze the strategic role of political party witnesses in maintaining the integrity of vote counting, identify the challenges they face, and recommend strategies to enhance their effectiveness. The study uses a qualitative-descriptive approach with in-depth interviews and document analysis. Data was obtained from political party witnesses, election organizers, and relevant documents. The findings indicate that witnesses play an essential role in preventing vote manipulation and reporting violations. However, they face challenges such as political pressure, limited technical training, and logistical issues, especially in remote areas. The study recommends intensive training, the use of technology, better legal protection, and collaboration with independent institutions to improve the effectiveness of witnesses. In conclusion, political party witnesses are a key element in ensuring the transparency and legitimacy of election results, and adequate support is needed to strengthen democracy in Indonesia.